Factors Influencing Students’ Interest in Starting a Business at Klabat University - Taliwongso, Indrajit; Sijabat, Lelasari (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
In the era of high business competitiveness and increasing unemployment from corporations, being an entrepreneur and starting their own business is one of the options for the student’s future. This study was conducted empirically to examine the influence of creativity, innovation, motivation, and knowledge on student interest in starting a business at Klabat University. The independent variables used in this study consisted of internal variables and external variables, where the internal factors are creativity, innovation, motivation, and knowledge as the external variable, whereas the dependent variable is the Students’ Interest in starting a business. This study used primary data gathered directly from the students of Klabat University who are taking entrepreneurship courses in the second term of the 2018/2019 academic year and those who are not to see various responses from students with different backgrounds, situations, and conditions. The statistical analysis method used to test this research is multiple regression analysis of t-test and f-test using SPSS software. The results of this study indicate that internal and external factors influence students’ interest in starting a business significantly. Keywords : Entrepreneurship, Creativity, innovation, motivation, knowledge, and students’ interest